Spectrum of Chest Computed Tomography findings of Novel Coronavirus disease 2019 in Medical City in Baghdad, a case series - Adnan, Atheer; Joori, Salam; Hammoodi, Zaid; Ghayad, Haider; Ibrahim, Ali (Journal of the Faculty of Medicine Baghdad, 2020)
Background: Native chest Computed Tomography (CT) is a quick, non-invasive and practical investigation & plays an important role in evaluation of Coronavirus Disease 2019. Objective: to describe the chest CT findings in patients with confirmed coronavirus disease 2019 (COVID-19) in sample from Baghdad population. Patients & methods: Study sample consisted of 55 patients with laboratory confirmed COVID-19 from 1st March through 15th April 2020. Native chest CT was performed in radiology departments in Medical City Teaching Complex (MCTH). The chest CT images were reviewed & analyzed. Results: The most frequent CT findings were ground-glass opacities (47.3%) & mixed ground glass & consolidation (43.6%). Most lesions were multiple (67.2%), peripheral (56.3%) & bilateral (81.8%). Least common findings were pleural effusion (7.2%) & mediastinal lymphadenopathy (1.8%). Conclusion: The commonest chest CT findings of COVID-19 in Baghdad population were multiple, bilateral, peripheral ground glass opacity & consolidation.